Combination of endometrial thickness and pipelle sampling in the diagnosis of endometrial disease in postmenopausal women? - (:unkn) unknown (My University, 1996)
In this article, we evaluate the value of the combined use of vaginal sonography and endometrial sampling for the diagnosis of endometrial disease in postmenopausal women. Fifty-three postmenopausal women presenting with uterine bleeding participated in this study. Sonographic measurement of the endometrium and endometrial biopsy with the Pipelle were performed before curettage. The accuracy of ultrasound and Pipelle sampling were measured against the final diagnosis. The sensitivity of vaginal ultrasonography for endometrial disease was 87.5%, using a cutoff point for endometrial thickness of 5 mm. Pipelle endometrial sampling had a sensitivity of 68%. The combined use of ultrasound and Pipelle sampling offered a sensitivity of 91%, and a specificity of 100%. © 1996 S. Karger AG, Basel.
Keywords: Endometrial thickness; Formal curettage; Pipelle sampling